2019
DOI: 10.1111/dme.14191
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different metabolic states and surgical models on glucose metabolism and secretion of ileal L‐cell peptides: results from the HIPER‐1 study

Abstract: Aim To compare the impact of four surgical procedures (mini‐gastric bypass, sleeve gastrectomy, ileal transposition and transit bipartition) vs medical management on gut peptide secretion, β‐cell function and resolution of hyperglycaemia in people with type 2 diabetes. Research design and methods A mixed‐meal tolerance test was administered 6–24 months after each surgical procedure (mini‐gastric bypass, sleeve gastrectomy, ileal transposition and transit bipartition; n=30 in each group) and the results were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
5
0
2
Order By: Relevance
“…Thus, we herein compare them to those of established MBS procedures. Publications reporting general SG-TB outcomes to date have found the procedure safe and effective in the early and medium terms 3–13. Our previous evaluation of SG-TB found a BMI of 27.6±2.7 kg/m 2 at the 4-year study end point (BMI change 7.5±2.8 kg/m 2 , P <0.001) and 79.2% complete T2DM remission (A1C<6.5%, off medications for 1 y) with a mean A1C of 6.3±0.5% (percentage decrease 36.7±11.6%) in 38 patients (86.4%).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, we herein compare them to those of established MBS procedures. Publications reporting general SG-TB outcomes to date have found the procedure safe and effective in the early and medium terms 3–13. Our previous evaluation of SG-TB found a BMI of 27.6±2.7 kg/m 2 at the 4-year study end point (BMI change 7.5±2.8 kg/m 2 , P <0.001) and 79.2% complete T2DM remission (A1C<6.5%, off medications for 1 y) with a mean A1C of 6.3±0.5% (percentage decrease 36.7±11.6%) in 38 patients (86.4%).…”
Section: Discussionmentioning
confidence: 96%
“…Publications reporting general SG-TB outcomes to date have found the procedure safe and effective in the early and medium terms. [3][4][5][6][7][8][9][10][11][12][13] Our previous evaluation of SG-TB found a BMI of 27.6 ± 2.7 kg/m 2 at the 4-year study end point (BMI change 7.5 ± 2.8 kg/m 2 , P < 0.001) and 79.2% complete T2DM remission (A1C < 6.5%, off medications for 1 y) with a mean A1C of 6.3 ± 0.5% (percentage decrease 36.7 ± 11.6%) in 38 patients (86.4%). In our current SG-TB study, BMI reduction and testosterone increase were significantly correlated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the few SG-TB reports to date [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 15 , 21 ], this procedure appears to effect marked weight loss and reduction of comorbid disease, particularly T2D, with minimal complications and without causing malnutrition. Recently, we reported initial outcomes of our complete SG-TB series performed in patients with class 1 and 2 obesity ( n = 883, mean preoperative BMI 34.1 ± 5.0 kg/m 2 ) and diagnosed T2D ( n = 883) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cagiltay et al 7 compared sleeve gastrectomy (SG), OAGB, ileal transposition, and SGTB. They demonstrated that SGTB had the lowest glucose elevations after a mixed meal, with the greatest beta cell responsiveness to glucose measured as ΔC-peptide/Δglucose 0-120 in transit bipartition.…”
Section: Introductionmentioning
confidence: 99%